Congregational missions and the making of an imperial culture in nineteenth-century England - Thorne, Susan, 1958- (Stanford University Press, 1999)
"This book explores the missionary movement's influence on popular perceptions of empire and race in nineteenth-century England. The foreign missionary endeavor was one of the most influential of the channels through which nineteenth-century Britons encountered the colonies, and because of their ties to organized religion, foreign missionary societies enjoyed more regular access to a popular audience than any other colonial lobby." "Focusing on the influential denominational case of English Congregationalism, this study shows how the missionary movement's audience in Britain was inundated with propaganda designed to mobilize financial and political support for missionary operations aboard, propaganda in which the imperial context and colonized targets of missionary operations figured prominently."--Jacket.